Persepsi Guru terhadap Pembentukan Karakter Peserta Didik: Kajian Sistematis Literatur - Bariroh, Zulaikah; Firdaus, Rifqi (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
This study aims to analyze teachers’ perceptions of character formation in students through the Systematic Literature Review (SLR) approach. Data were taken from five journal articles relevant to the topic, published between 2020 and 2024. The results of the study indicate that the role of teachers is very significant in shaping students' character through the integration of values ​​such as responsibility, honesty, discipline, love, and caring in the learning process. Modern technology, such as multimedia, has the potential to support character building, but requires infrastructure readiness and teacher training. Religious values ​​are also a strong foundation in character education, especially at an early age level, to instill morals and ethics. However, the influence of technology, external culture, and lack of supervision are challenges in maintaining students' character. Character surveys in national assessments are considered useful for understanding students' character comprehensively and helping teachers design more effective learning. This study recommends ongoing teacher training, integration of character values ​​in the curriculum, wise use of technology, and collaboration between schools, families, and communities to create an educational ecosystem that supports the formation of students’ character.